2007
DOI: 10.4049/jimmunol.178.9.5859
|View full text |Cite
|
Sign up to set email alerts
|

Induction of IL-13 Triggers TGF-β1-Dependent Tissue Fibrosis in Chronic 2,4,6-Trinitrobenzene Sulfonic Acid Colitis

Abstract: To investigate the immunopathogenesis of inflammation-associated fibrosis, we analyzed the chronic colitis and late-developing fibrosis occurring in BALB/c mice administered weekly doses of intrarectal 2,4,6-trinitrobenzene sulfonic acid. We showed first in this model that an initial Th1 response involving IL-12p70 and IFN-γ subsides after 3 wk to be supplanted by an IL-23/IL-25 response beginning after 4–5 wk. This evolution is followed by gradually increasing production of IL-17 and cytokines ordinarily seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
203
5
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(239 citation statements)
references
References 59 publications
24
203
5
7
Order By: Relevance
“…Our results are in line with that of TNBS-induced colitis whereby both IL-25 and IL-23 were shown to appear together (21). In this most recent study, IL-25 was reported to facilitate the production of TGF-1 through induction of IL-13 (21).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in line with that of TNBS-induced colitis whereby both IL-25 and IL-23 were shown to appear together (21). In this most recent study, IL-25 was reported to facilitate the production of TGF-1 through induction of IL-13 (21).…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in line with that of TNBS-induced colitis whereby both IL-25 and IL-23 were shown to appear together (21). In this most recent study, IL-25 was reported to facilitate the production of TGF-1 through induction of IL-13 (21). TGF-1 has long been recognized to exert an anti-inflammatory effect and under certain conditions potentates inflammation (22).…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, IL-13 is hypothesized to execute its IL-4R␣-dependent effects solely through the type II IL-4R but may use a signaling complex that does not require IL-4R␣ (3). In addition, IL-13R␣2, an IL-13 decoy receptor (4), has been recently reported to also mediate IL-13 signaling and induce TGF-␤ production (5,6). Thus, the assumption that IL-13R␣1 is the main signaling receptor for IL-13 needs definitive proof.…”
mentioning
confidence: 99%
“…Accumulating evidence also suggests that Th17 cells have a pathogenic role in experimental models of IBD. For example, up -regulation of IL -17 occurs in mice with acute and relapsing TNBS colitis, and blockade of IL -17R signals protects animals against the development of acute TNBS colitis 32,33) . We have also shown that administration of NE inhibitor suppresses expression of IL -17 in the colon.…”
Section: Discussionmentioning
confidence: 99%